Effect of Plyometric Training on Sport Performance in Adolescent Overhead Athletes: A Systematic Review. (January 2021) - Eraslan, Leyla; Castelein, Birgit; Spanhove, Valentien; Orhan, Ceren; Duzgun, Irem; Cools, Ann
Context: Plyometric training has been shown to be beneficial in adolescent overhead athletes. However, existing research on the effects of plyometrics on sport performance has been limited. Objective: To systematically review the current literature to investigate whether plyometric training intervention improves upper- and lower-body sport performance. Data Sources: Two electronic databases (MEDLINE and Web of Science) were searched using specific Medical Subject Headings (MeSH) terms up to February 2019, and hand-searching was performed by looking to relevant studies that were cited in other studies. Study Selection: A total of 932 items were identified and were further assessed for the eligibility in the systematic review. For a study to be eligible, each of the following inclusion criteria had to be met: (1) participants were aged 13 to 18 years and selected from a sports or athletic population and the study (2) involved the evaluation of a plyometric training intervention with an aim to improve sports performance; (3) must have included a control intervention and/or control group; (4) included a quantitative objective measure of sport performance variables concerning throwing, jumping, running, and sprinting; and (5) was published in English. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: A first screening was conducted based on title and abstract of the articles. In the second screening, the full text of the remaining articles was evaluated for the fulfillment of the inclusion criteria. Results: A total of 14 studies were included in this review. The methodological quality of the included studies ranged from low to moderate. There is moderate evidence that plyometric training intervention improves throwing and jumping performances. There is also preliminary evidence that plyometric training intervention improves sprint performance. Conclusion: The current evidence suggests that sport performance consisting of throwing capacity, jumping ability, and sprint performance significantly improved due to plyometric training interventions in adolescent overhead athletes.